2020
DOI: 10.1177/1559325820942075
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic Analysis of Methylation and Transcriptome Reveals a Novel Signature in Esophageal Cancer

Abstract: Background: Epigenetic alterations have been shown to lead to human carcinogenesis. The aim of this study was to perform an integrative analysis to develop an epigenetic signature to predict overall survival (OS) of esophageal cancer. Methods: DNA methylation and messenger RNA expression data of esophageal cancer samples were downloaded from The Cancer Genome Atlas database and were incorporated and analyzed using an R package MethylMix. Functional enrichment analysis of the methylation-related differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Some studies have incorporated the nutritional information and inflammatory profile of patients into the nomogram and successfully demonstrated that the developed nomogram has a better performance than the TNM staging system ( 6 , 21 , 22 ). In addition, other studies have incorporated genomic data, such as DNA methylation ( 23 ), long non-coding RNA ( 24 ), and autophagy-related gene data ( 25 ), into the nomogram and successfully shown that the developed nomogram has a better discrimination ability than the TNM staging system. However, no studies have incorporated ctDNA mutation information into nomogram models.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have incorporated the nutritional information and inflammatory profile of patients into the nomogram and successfully demonstrated that the developed nomogram has a better performance than the TNM staging system ( 6 , 21 , 22 ). In addition, other studies have incorporated genomic data, such as DNA methylation ( 23 ), long non-coding RNA ( 24 ), and autophagy-related gene data ( 25 ), into the nomogram and successfully shown that the developed nomogram has a better discrimination ability than the TNM staging system. However, no studies have incorporated ctDNA mutation information into nomogram models.…”
Section: Discussionmentioning
confidence: 99%
“…EC is the most common malignant tumor of the digestive tract and has a poor prognosis. Studies have established several novel biomarkers to determine the prognosis of EC patients, such as miRNA signatures 7,8 , autophagy-related signatures 9 , m6A RNA methylation regulator-based signatures 10 , integrated mRNA-lncRNA signatures 11 , epigenetic signatures 12 , lymph node metastasis-associated gene signatures 13 , urinary metabolomic signatures 14 , and immune-related gene signatures 15 . Although RBPrelated signatures have been analyzed for a variety of cancers [16][17][18][19][20][21] , related analyses for EC are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DNA methylation may become one of the methods for early diagnosis of EAC. Recently, a study on EC established an epigenetic signature to evaluate the prognosis of EC [ 34 ]. However, the prognostic model for EAC alone is still lacking.…”
Section: Discussionmentioning
confidence: 99%